Purinosomes involved in the regulation of tumor metabolism: current progress and potential application targets - Xie, Jiaqi; Liu, Jiaqi; Chen, Xiehui; Zeng, Changchun (Frontiers in Oncology, 2024)
The core of tumor cell metabolism is the management of energy metabolism due to the extremely high energy requirements of tumor cells. The purine nucleotide synthesis pathway in cells uses the purinosomes as an essential spatial structural complex. In addition to serving a crucial regulatory role in the emergence and growth of tumors, it contributes to the synthesis and metabolism of purine nucleotides. The significance of purine metabolism in tumor cells is initially addressed in this current article. The role of purinosomes as prospective therapeutic targets is then reviewed, along with a list of the signaling pathways that play in the regulation of tumor metabolism. A thorough comprehension of the function of purinosomes in the control of tumor metabolism can generate fresh suggestions for the creation of innovative cancer treatment methods.